Segurança e efeito probiótico de Weissella paramesenteroides WpK4 isolada de suíno na infecção experimental com Salmonella Typhimurium em camundongos - Luige Biciati Alvim (2015)
Diarrhea in piglets by Salmonella spp. and other pathogens can be a serious problem and require prevention and treatment. Antimicrobials have been used to combat these infections; however, the induction of bacterial resistance due to the undiscriminating use of sub-therapeutic doses into animal food has led governor authorities to prohibit these traditional growth promoters. Thus, probiotics have emerged as potential substitutes, as they provide benefits to the intestinal microbiota and show immunomodulatory capacity in its host. The aim of this study was to select autochthonous strains of Lactic Acid Bacteria (LAB) isolated from healthy piglets according to their probiotic properties and safety for further use as a food supplement for piglets as a non-drug therapy for controlling gastrointestinal microbiota dysbiosis and stimulating host immune system. Twenty-four LAB of Lactobacillus and Weissella genera isolated from oral and nasal mucosa and feces of piglets were previously identified and subjected to in vitro assays. In this work, strains were in vitro tested for hydrogen peroxide production, exopolysaccharide synthesis, antimicrobial susceptibility and isoantagonistic activity. The Weissella paramesenteroides WpK4 was considered to be the most promising probiotic candidate, as it presented high resistance to acidic pH and bile salts, a hydrophobic cell surface, H2O2 and EPS production, strong antagonism against bacterial pathogens, and only intrinsically-encoded antibiotic resistance (oxacillin and vancomycin). Thus, it was selected for in vivo trials in an experimental mouse model of salmonellosis. Conventional and germ-free mice fed with WpK4 showed no signs of bacterial translocation to the liver or spleen and decreased salmonella translocation to these organs. Significantly, WpK4 colonization attenuated the weight loss, fostered the preservation of intestinal architecture and integrity, and promoted survival in mice following infection with Salmonella Typhimurium. In addition, WpK4 modulates immune response by inhibiting the production of pro-inflammatory cytokines and induce anti-inflammatory mediators. These findings validate the suitable probiotic properties of the W. paramesenteroides WpK4 strain, and provide for its eventual use in piglets.